Atrial fibrillation and stroke outcomes in Scotland: real-world evidence from a contemporary, national dataset. (25th November 2020) - Ciminata, G; Venson, R; Geue, C; Quinn, T; Trotter, R; Pollock, K; Lister, S
Abstract: Introduction: Atrial Fibrillation (AF) is an important cause of mortality and morbidity. The major risk of AF is stroke, which can be reduced through anticoagulation. The burden of stroke, and AF-related stroke, is particularly high in Scotland. It is often reported that AF-related stroke is associated with poorer outcomes than other stroke types, it is also thought to lead to an increased institutionalisation. Data supporting these observations are historic, but major advances in AF assessment and treatment could have changed outcome patterns. Real world evidence on outcomes, collected at scale, can give a useful measure of contemporary AF stroke outcomes. Purpose: To assess whether stroke patients, with and without AF on admission, differ in terms of al-cause mortality, recurrence of stroke, and care home admission using contemporary large-scale observational data. Methods: A retrospective cohort study linking national hospital, prescribing, care home and stroke audit data was conducted. The cohort, comprising patients ≥18 years of age with incident ischemic stroke between 2009 and 2017, was divided into three groups: AF-related stroke prescribed oral anticoagulant (OAC) pre-stroke event (AF-OAC Group); AF-related stroke not prescribed anticoagulant pre-stroke event (AF-noOAC Group); stroke with no prevalent or incident AF and no anticoagulation (comparator) (noAF-noOAC Group). Time-to-event analyses (adjusted for demographic and clinical characteristics) were conducted to estimate hazard ratios for recurrent stroke, all-cause mortality, and care-home admission with a follow-up time of two years. Results: From a cohort of 64, 159 incident ischemic strokes, 4, 418 and 15, 124 patients with AF were identified for groups AF-OAC and AF-noOAC, respectively. The remaining 44, 617 patients belonged to group noAF-noOAC. An increasing number of incident strokes was observed with increasing age in each group up to 80–84 years. The risk of recurrent stroke was significantly greater in groups AF-OAC (HR 1.12 [95% CI 1.08, 1.17]) and AF-noOAC (HR 1.05 [95% CI 1.03, 1.08]) compared to noAF-noOAC group. An increased risk of all-cause mortality was observed in groups AF-OAC (HR 1.52 [95% CI 1.39, 1.66]) and AF-noOAC (HR 1.59 [95% CI 1.51, 1.68]) compared to the noAF-noOAC group. Patients in group AF-noOAC were more likely to be discharged to a care home following stroke (HR 1.37 [95% CI 1.23, 1.52]) compared to patients in the other groups. Conclusion: AF-related stroke is associated with poor outcomes, with significantly higher risks of recurrent stroke and all-cause mortality for patients with AF compared to non-AF stroke. Despite advances in AF care, our data suggest there is still potential to prevent a substantial proportion of disabling strokes through better identification and treatment of AF. These results must be interpreted with caution, as data take no account of treatment adherence, dosing or rationale for individual patient level prescribing decisions. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Bristol-Myers Squibb Research and Development